The relationships between scrotal surface temperature, age and sperm quality in stallions - Ramires Neto, Carlos [UNESP]; Monteiro, Gabriel Augusto [UNESP]; Zanzarini Delfiol, Diego José [UNESP]; Farras, Marcel Cavalcanti [UNESP]; Dell'aqua Junior, José Antônio [UNESP]; Papa, Frederico Ozanam [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2013)
In horses, spermatogenesis normally occurs at an average intratesticular temperature of 35. °C; therefore, mechanisms for testicular thermoregulation are essential. Measuring the scrotal surface temperature by thermography is one of the methodologies used to evaluate the effectiveness of testicular thermoregulation. The objective of this study was to determine the relationship between the control of scrotal surface temperature and sperm quality in horses of different ages. In total, 24 Quarter Horse stallions were divided into three groups: YS (young stallions), AS (adult stallions) and OS (old stallions). Initially, we calculated the testicular volume (TV) and evaluated various aspects of the semen (sperm kinetics, plasma membrane integrity and sperm morphology) for all the animals. We also evaluated rectal temperature (RT), body surface temperature (BST,) and average scrotal surface temperature in the testicular region (SST) before (M0) and after sun exposure (M1). Differences were observed (p<0.05) between the RT and BST before and after sun exposure in all three groups. However, there were no differences (p>0.05) in the SST values at these two time points, thus demonstrating the efficiency of the mechanisms for testicular thermoregulation. The SST was similar (p>0.05) among all three groups. Based on these results, we conclude that fertile stallions of different age groups are able to maintain SST and measuring the heat radiating from the scrotum using a digital infrared thermographer. We can also conclude that measuring the heat radiating from the scrotum using a digital infrared thermographer is a practical and efficient tool for monitoring SST in horses. © 2013 Elsevier B.V.
Keywords: Horse; Semen; Testicle; Thermography; Thermoregulation; Animalia; Equidae